Attribute Non-Attendance and Consumer Preferences for Online Food Products in Germany - P. Christoph Richartz; Awudu Abdulai; Lukas Kornher (German Journal of Agricultural Economics (GJAE), 2020)
In this article, we apply a choice experiment method to examine consumers' preferences for online food product attributes, using survey data for German consumers for meat products. We use both mixed logit and latent class models to analyze preference heterogeneity and sources of heterogeneity, as well as endogenous attribute attendance models to account for consumers' attribute processing strategies. The empirical results reveal significant heterogeneity in preferences for online meat attributes among consumers. We also find that consumers' willingness to pay estimates are highly influenced by their attribute processing strategies.
Keywords: 330